Faktor Yang Mempengaruhi Kualitas Laporan Dana BOP Sekolah - Nisrina, Wida; Pravasanti, Yuwitta Ariessa; Ma’ruf, Muhammad Hasan (Nur Science Institute, 2024)
This research aims to examine the influence of human resource competence, internal control systems, and the use of information technology on the quality of school Operational Assistance fund reports in Boyolali Regency. This type of research includes quantitative research using primary data obtained directly by respondents using questionnaires. The population in this study was the school principal and treasurer of school Operational Assistance Raudhotul Athfal in Boyolali Regency. Respondents in this study were 62 respondents. The technique used in this sampling was the Purposive Sampling technique. The data analysis techniques used are descriptive statistics, instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The research results show that human resource competency has a significant effect on the quality of school Operational Assistance fund reports. The internal control system does not have a significant effect on the quality of school Operational Assistance fund reports. And the use of information technology has a significant effect on the quality of school Operational Assistance fund reports.